Characterisation of the transient mixing behaviour of evaporating near-critical droplets - Steinhausen, Christoph; Gerber, Valerie; Stierle, Rolf; Preusche, Andreas; Dreizler, Andreas; Gross, Joachim; Weigand, Bernhard; Lamanna, Grazia (Frontiers in Physics, 2023)
With technical progress, combustion pressures have been increased over the years, frequently exceeding the critical pressure of the injected fluids. For conditions beyond the critical point of the injected fluids, the fundamental physics of mixing and evaporation processes is not yet fully understood. In particular, quantitative data for validation of numerical simulations and analytical models remain sparse. In previous works, transient speed of sound studies applying laser-induced thermal acoustics (LITA) have been conducted to investigate the mixing behaviour in the wake of an evaporating droplet injected into a supercritical atmosphere. LITA is a seedless, non-intrusive measurement technique capable of direct speed of sound measurements within these mixing processes. The used setup employs a high-repetition-rate excitation laser source and, therefore, allows the acquisition of time-resolved speed of sound data. For the visualisation of the evaporation process, measurements are accompanied by direct, high-speed shadowgraphy. In the present work, the measured speed of sound data are evaluated by applying an advection-controlled mixing assumption to estimate both the local mole fraction and mixing temperature. For this purpose, planar spontaneous Raman scattering results measured under the same operating conditions are evaluated using an advection-controlled mixing assumption with the perturbed-chain statistical associating fluid theory (PC-SAFT) equation of state. Successively, the resulting concentration–temperature field is used for the estimation of local mixture parameters from the detected speed of sound data. Moreover, models using the PC-SAFT equation of state and the NIST database for the computation of the speed of sound are compared. The investigations indicate a classical two-phase evaporation process with evaporative cooling of the droplet. The subsequent mixing of fluid vapour and ambient gas also remains subcritical in the direct vicinity of the droplet.